Simulated structure and imaging of NTCDI on Si(1 1 1)-7 × 7 : a combined STM, NC-AFM and DFT study - Jarvis, Samuel Paul; Sweetman, Adam; Lekkas, Ioannis; Champness, Neil R.; Kantorovich, Lev; Moriarty, Philip (IOP Publishing, 2015)
The adsorption of naphthalene tetracarboxylic diimide (NTCDI) on Si(1 1 1)-7 × 7 is investigated through a combination of scanning tunnelling microscopy (STM), noncontact atomic force microscopy (NC-AFM) and density functional theory (DFT) calculations. We show that NTCDI adopts multiple planar adsorption geometries on the Si(1 1 1)-7 × 7 surface which can be imaged with intramolecular bond resolution using NC-AFM. DFT calculations reveal adsorption is dominated by covalent bond formation between the molecular oxygen atoms and the surface silicon adatoms. The chemisorption of the molecule is found to induce subtle distortions to the molecular structure, which are observed in NC-AFM images.